Emotional regulation and violence among dating youth in Huancayo, Peru - Aparco Osorio, Yaki Elen (2024)
Objective. To determine the relationship between emotional regulation and violence among dating couples in young people from a higher education institute in Huancayo, 2023. Methods. The method was quantitative, non-experimental, and correlational. The sample consisted of 262 young people of both sexes who are in a romantic relationship. They were assessed using the Emotional Regulation Questionnaire (ERQ), which has 10 questions, and the Dating Violence Questionnaire (CUVINO, by its Spanish acronym), which has 29 questions; both with reliability and validity. Spearman's r test was used for inferential analysis, with a signifcance value of p = 0.05. Results. It was evident that there is a statistically significant correlation between emotional regulation and violence among dating couples (0.003; p < 0.05). The cognitive reappraisal dimension is related to violence among dating couples (0.038; p < 0.05); emotional regulation is related to the dimensions: manipulation (0.40; p < 0.05), psychological violence (0.36; p < 0.05), physical violence (0.43; p < 0.05), and prohibition (0.003; p < 0.05). Conclusions. Emotional regulation is a predictor of violence among dating couples; greater emotional regulation correlates with less abuse and a greater ability to identify types of violence in their romantic relationships.